ROLE OF FOREIGN DIRECT INVESTMENT IN INNOVATIVE DEVELOPMENT OF THE AGRARIAN SECTOR - Marianna VASILCHENKO; Ivan SANDU; Vladimir DERUNOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Overcoming the shortage of investment resources for the development of the agro-industrial complex of Russia makes it necessary to mobilize both internal and external sources of investment. Attracting foreign direct investment in the agro-industrial complex, creating favorable conditions is one of the most difficult tasks. The purpose of the study is to assess the available mechanisms to stimulate the attraction of foreign investment and determine their contribution to the innovative development of the agricultural sector and increasing the possibilities of food exports; identification of the relationship between the scale of foreign direct investment and the investment attractiveness of Russian regions. Studied foreign and domestic theoretical and methodological approaches to assessing the conditions, opportunities and limitations of foreign direct investment, macroeconomic and globalization effects from their use. The necessity of increasing the inflow of foreign investment in agriculture in order to activate the process of innovative structural transformation of the Russian economy has been substantiated. Investigated the provision of foreign investments in agriculture. An empirical assessment of the scale of foreign investment in agriculture has been carried out, measures are proposed to stimulate the attraction of foreign investment in agriculture. The practical significance of the results of this study lies in the development of measures to improve investment policy in relation to foreign direct investment.